Training Factors within the Ontario Manufacturing Sector - LeBrasseur, Rolland; Lambert, Marie-Josée (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
This article presents the results of a survey of the Ontario manufacturing sector, and identifies intra- and extra- organizational factors influencing the training activities of firms. On average, employees received 2,6 days of directly provided training, and some supported training. It was concluded that improvement in training participation rates has taken place throughout the 1980s, and that leading companies are reaching new levels in the duration of training offered. A variety of factors, such as Management Commitment, were found to be significant predictors of training activities.